A contextual analysis of the emergence of social studies education and the advancement of cybercrime (yahoo- yahoo) in the Nigerian society (2020)
Technology has merged nations of the world into a global village and has made the socioeconomic and cultural activities of many nations are easily accessible. With its advent, there has been positive internet revolution as well as many maladies and atrocity which threaten social order and tranquility enjoyed in the society. Nigeria is now known as hotspot for cybercrimes with new waves of engaging in criminalities. The focus of Social Studies discipline is to correct the abnormalities in the society as well as create a new reaction to the inadequacies of past practices with particular reference to inculcation of desirable norms, skills, knowledge, values and rights attitudes for sustenance of individual and societal growth But with the emergence of the discipline and its lofty objectives, the menace of cybercrime is still unmatched by every standard and measure. Findings show that most Nigerian youths are now rooted and grounded in criminality and have vast experience in defrauding people using the internet mechanism. However, it is not peculiar to Nigeria alone in Africa or the world at large but its embrace is significantly greater than what anyone can ever imagine. The study carefully perused qualitatively literature in journals, textbooks, and oral interviews. The study therefore recommends that Social Studies as a school discipline on corrective journey must live up to expectations in terms of national orientations, incorporation of cybercrime concepts, themes and topics in creating teenagers and youths awareness of the nefarious act, advocating dignity of labour and de-emphasizing the get-rich-quick syndrome. It also advocate for strong measures, viable policies and programmes on poverty reduction and eradication mechanism which must be judiciously backed by actions and measure. The study finally reminded that unemployment has to be dealt with to get rid of this cybercrime.